Proposed Airport Agreement - Paul E. Wolven:::::: (1971)
A memorandum informing the Oxnard City Council of background information for the proposed airport in the former Oxnard Air Force Base. Includes an advantages and disadvantages list, a report on possible noise pollution, and a cooperative agreement between County of Ventura and City of Oxnard.